2007
DOI: 10.1074/jbc.m702125200
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Integrin Affinity and Integrin-Cytoskeletal Engagement in Endothelial and Smooth Muscle Cell Adhesion to Vitronectin

Abstract: The serine proteinase inhibitor, plasminogen activator inhibitor type-1 (PAI-1), binds to the adhesion protein vitronectin with high affinity at a site that is located directly adjacent to the vitronectin RGD integrin binding sequence. The binding of PAI-1 to vitronectin sterically blocks integrin access to this site and completely inhibits the binding of purified integrins to vitronectin; however, its inhibition of endothelial and smooth muscle cell adhesion to vitronectin is at most 50 -75%. Because PAI-1 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…A recent study has shown that cells adhering to vitronectin in the presence of PAI1 are only partially inhibited from attachment (Stefansson et al, 2007). Those cells that can overcome the inhibitory effects of PAI1 on adhesion are partially spread and do not assemble either focal contacts or stress fibers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that cells adhering to vitronectin in the presence of PAI1 are only partially inhibited from attachment (Stefansson et al, 2007). Those cells that can overcome the inhibitory effects of PAI1 on adhesion are partially spread and do not assemble either focal contacts or stress fibers.…”
Section: Discussionmentioning
confidence: 99%
“…These are components of ECM and their upregulation indicates that they could be playing a role in stronger adherence of blebbistatin-treated cells to the substratum [20,21]. Similarly, VTN, a serum-spreading protein responsible for spreading of cells and adhesion [22], was found to be upregulated in our blebbistatin-treated WJ-MSCs, which by morphology were flattened and more spread out than the control WJ-MSCs. MMPs play a role in the turnover and degradation of ECM components and basement membranes, which influences many biological processes such as proliferation, migration, and angiogenesis [23].…”
Section: Nmii Regulates Migration Of Wj-mscs 2075mentioning
confidence: 66%
“…It is possible that competition between PAI-1 and cell membrane integrin already bound to vitronectin favors the latter because of its higher affinity. Once bound to its ligand, the integrin-mediated endothelial cell adhesion is further strengthened by the formation of cell-substratum focal contacts (35). During active angiogenesis and in the newly established vasculature, however, angiogenic endothelial cells actively break focal contact and further readhesion to vitronectin is inhibited by a high local concentration of PAI-1 in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%